Ecotoxicology: problems and approaches - Levin, A, Simon | Harwell, Mark A | Kelly, John R. | Kimball, Kenneth D. (Estados Unidos | ESTADOS UNIDOS Springer-Verlag / New York, 1989)
This book conveys to the reader an up to date overview of the science of ecotoxicology which describes and predicts ecological changes resulting from a variety of human activities involving release of xenobiotic and other chemicals to the environment.
Sin Especificar
Keywords: Toxicología | Contaminación-Aspectos ambientales